Flexible wearable intelligent sensing system for wheelchair sports monitoring - Mao, Y.; Wen, Y.; Liu, B.; Sun, F.; Zhu, Y.; Wang, J.; Zhang, R.; Yu, Z.; Chu, L.; Zhou, A. (iScience, 2023)
The application of wearable intelligent systems toward human-computer interaction has received wide spread attention. It is still desirable to conveniently promote health and monitor sports skills for disabled people. Here, a wireless intelligent sensing system (WISS) has been developed, which includes two ports of wearable flexible triboelectric nanogenerator (WF-TENG) sensing and an upper computer digital signal receiving intelligent processing. The WF-TENG sensing port is connected by the WF-TENG sensor and flexible printed circuit (FPC). Due to its flexibility, the WF-TENG sensing port can be freely adhered on the surface of human skin. The WISS can be applied to entertainment reaction training based on hu man-computer interaction, and to the technical judgment and analysis on wheelchair curling sport. This work provides new application opportunities for wearable devices in the fields of sports skills monitoring, sports assistive devices and health promotion for disabled people.